Challenging The City Scale. Journeys in People-Centred Design - Cité du Design (Birkhäuser - an imprint of De Gruyter, 2018)
Since 2014, the Human Cities network has been working on Challenging the City Scale: a pan-European project led by Cité　du design Saint-Étienne and supported by the Creative Europe programme to question the urban scale and investigate co-creation in cities. The Human Cities partners have carried out urban experimentations in 11 European cities empowering citizens to rethink the spaces in which they live, work and spend their leisure time. Through conversations with people involved, the book examines how bottom-up processes and their design, tools and instruments generate new ideas to reinvent the city. It offers inspiration and insights to everyone, from practitioners and politicians to designers and active citizens, eager to try out new ways to produce more human cities together.